Analisa Perbandingan Hasil Belajar Menggunakan Media Pembelajaran Berbasis E-Learning Edmodo dengan Schoology terhadap Hasil Belajar Peserta Didik pada Mata Pelajaran Dasar Listrik dan Elektronika Jurusan Elektronika Industri SMK Ananda Mitra Industri - Diva Jannah, Adila; Sukardjo, Moch; Ma'Sum, Mufti (JURNAL PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA (JVoTE), 2023)
This study aims to compare the learning outcomes of basic electrical and electronic learning using Schoology and Edmodo-based e-learning. The research method used in this study was a true experiment design, with a pretest-posttest control group design. The student population and sample consisted of two classes using simple random sampling. The data collection technique used a test instrument. The results showed a difference in the posttest mean of the Schoology class of 67.98 and the Edmodo class of 56.07. The t-test calculation yielded a calculated t of 2.018, and a t-table value of 1.9934 with a 5% significance level (dk=72). Therefore, H0 (calculated t > t-table) was rejected. The posttest result for the experimental class was 67.98, indicating that Schoology-based e-learning was superior to Edmodo. The conclusion of this study is that there is a difference in student learning outcomes using the E-learning learning media Schoology and Edmodo.